Self-perceived stigma and its effect on quality of life among Malaysians living with human immunodeficiency virus - Nadia Abdul Bari,; Leelavathi Muthupalaniappen,; Narul Aida S,; Diana M, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Human Immunodeficiency Virus (HIV) epidemic remains a significant burden in Malaysia. Stigma related to HIV and its effect on the quality of life (QOL) of persons living with HIV (PLHIV) remains under-reported. The aim of the present study was to assess self-perceived stigma amongst PLHIV attending an urban community clinic and its influence on their QOL. Data was collected using HIV Stigma Scale and WHO-QOL HIV BREF Scale. The overall stigma experienced by PLHIV in this community was higher than previous studies (mean ± SD; 103.37 ±18.14). Majority participants had fear disclosing their disease status, while personalized stigma or the experience of prejudice and rejection was the least experienced. The overall QOL was low and was significantly impaired in social relationship domain (mean ± SD; 12.72 ± 3.59). However, their ability to perform daily activities was not affected by the illness (mean ± SD; 14.48 ± 2.91). PLHIV with higher spiritual values demonstrate lower perception of negative self-image and inferiority (r= -0.54). This finding was unique to PLHIV in this study and suggested the importance of spirituality and personal beliefs on their self-esteem. In conclusion, stigma remains as a significant problem among PLHIV in this community. Primary care offers the best platform to promote a holistic management of PLHIV, where the integration between counselors, religious experts, family and non-governmental associations could come together. The management of PLHIV is unique in every community, hence individualized approach based on cultural norms and beliefs could assist in the overall management of PLHIV.